2011
DOI: 10.1016/j.ejvs.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Radiation Doses During the Implantation of Stents in Carotid, Renal, Iliac, Femoral and Popliteal Arteries

Abstract: In procedures performed on the arteries of the lower limbs, a significantly higher dose was received by patients with TASC II C lesions. With regard to the number of stents implanted, the total DAP value was 50% higher for simultaneous three-stent implantation than for one or two stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…9 Therefore, the relationship between CBCT radiation and the total procedure radiation dose is relatively high unlike the situation when using standard fluoroscopy and DSA. Majewska 16 This study used a higher radiation dose than the present study when comparing their results on iliac interventions, even when not subtracting the added CBCT radiation from the total amount of radiation. However, Majewska et al evaluated their interventions only in an antero-posterior setting, thus minimizing the scatter effect by not rotating the C-arm.…”
Section: Discussionmentioning
confidence: 91%
“…9 Therefore, the relationship between CBCT radiation and the total procedure radiation dose is relatively high unlike the situation when using standard fluoroscopy and DSA. Majewska 16 This study used a higher radiation dose than the present study when comparing their results on iliac interventions, even when not subtracting the added CBCT radiation from the total amount of radiation. However, Majewska et al evaluated their interventions only in an antero-posterior setting, thus minimizing the scatter effect by not rotating the C-arm.…”
Section: Discussionmentioning
confidence: 91%
“…In the most extensive study to date, AK and DAP were reported during stent insertion in different anatomic locations. 26 No direct comparison was performed between the various anatomic locations; however, the reported iliac procedure DAP ranged from 53-199 Gy*cm 2 and popliteal procedure DAP averaged only 63 Gy*cm 2 . In another study, an analysis of AK in lower extremity diagnostic procedures was performed with consideration given to anatomic disease location.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the radiation doses measured in percutaneous transhepatic billiary drainage insertion and therapeutic dialysis arteriovenous fistulography performed by our operators compare favorably to the best of previously published data. 15,[20][21][22][23]26 Next, we used DAP as a measure of patient radiation exposure. DAP is calculated by the integration of the AK across the entire X ray beam, but it does not include backscatter.…”
Section: Discussionmentioning
confidence: 99%
“…Die aus den Datensätzen des DeGIR-QM-Systems ermittelten Dosiswerte und Durchleuchtungszeiten entsprechen sehr gut denen der rezenten Literatur: Molyvda-Athanasopoulou et al [13] geben für die untere Extremität DFP-Werte von 1348 -8276 cG×cm 2 und DL-Zeiten von 10,2 -13,8 min an, wobei einschränkend erwähnt werden muss, dass hier nur 2 Eingriffe aufgeführt sind und somit diese Werte wenig repräsentativ sein dürften. Majewska et al [14] haben dagegen das DFP und die DL-Zeiten bei insgesamt 473 Prozeduren gemessen. Die behandelten Läsionen waren in der Beckenregion, der AFS und der A. poplitea lokalisiert und wurden nach den TASC-II-Kriterien in A, B, und C unterteilt.…”
Section: Strahlendosis Des Patientenunclassified